A Dynamic Panel Data Approach to the Forecasting of the GDP of German Länder - Konstantin Arkadievich Kholodilin; Boriss Siliverstovs; Stefan Kooths (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
In this paper, we make multi-step forecasts of the annual growth rates of the real GDP for each of the 16 German Länder (states) simultaneously. Beside the usual panel data models, such as pooled and fixed-effects models, we apply panel models that explicitly account for spatial dependence between regional GDP. We find that both pooling and accounting for spatial effects helps substantially improve the forecast performance compared to the individual autoregressive models estimated for each of the Lander separately. More importantly, we have demonstrated that effect of accounting for spatial dependence is even more pronounced at longer forecasting horizons (the forecast accuracy gain as measured by the root mean squared forecast error is about 9% at 1-year horizon and exceeds 40% at 5-year horizon). Hence, we strongly recommend incorporating spatial dependence structure into regional forecasting models, especially, when long-term forecasts are made.
Keywords: C21; C53; C23; 330; German Länder; forecasting; dynamic panel model; spatial autocorrelation